The Immersive Experience of the Era of Nuclear Energy in Emilija Škarnulytė’s Ecodocumentary Burial (2022) - Šukaitytė, Renata (Acta Academiae Artium Vilnensis, 2024)
The article examines Emilija Škarnulytė’s essay documentary Burial (Kapinynas, 2022) and its unique approach to engaging the audience with the themes of nature, atomic energy, and the nuclear era. It discusses how immersive techniques of aural and visual narrative, consisting of visual and acoustic material from diverse sources, such as images of former uranium mines in Kowary, the decommissioned Ignalina Nuclear Power Plant, The Industrial Centre for Geological Disposal in France, fragments of paintings by Lithuanian symbolist M. K. Čiurlionis, Cold War-era television and radio footage, computer-generated 3D images of atoms and uranium ore, and ambient music, can stimulate emotional and intellectual responses to its subject, even though there are no characters to identify with and no clear plot or strong rhetorical devices to direct the viewer. The use of immersive technologies in Škarnulytė’s film creates the sense of a “living” environ- ment experienced in “real time,” drawing on terms introduced by Oliver Grau (2003). The article’s conclusions are based on a close examination of the film’s style and narrative, as well as theoretical work on immersive films and media by Oliver Grau (2003) and Kerric Harvey (2012). The concepts of ecocinema (Paula Willoquet-Maricondi, 2010), eco-cosmopolitan cinema (Ursula K. Heise, 2008), and the essay film (Laura Rascaroli, 2017) are chosen as the theoretical framework for analysing Burial.